2023
DOI: 10.1021/acs.est.3c00959
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide Nanoparticles Improve Soybean Yield and Enhance Nitrogen Assimilation

Abstract: Nickel (Ni) is a trace element beneficial for plant growth and development and could improve crop yield by stimulating urea decomposition and nitrogen-fixing enzyme activity. A full life cycle study was conducted to compare the long-term effects of soil-applied NiO nanoparticles (n-NiO), NiO bulk (b-NiO), and NiSO4 at 10–200 mg kg–1 on plant growth and nutritional content of soybean. n-NiO at 50 mg kg–1 significantly promoted the seed yield by 39%. Only 50 mg kg–1 n-NiO promoted total fatty acid content and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Compared with the seed and leaf application methods, studies on soil Ni fertilization are more advanced, with a range of growing environments, soil classes and soybean genotypes having been evaluated previously (Table 3 ). It has been reported in the literature that this method improves N metabolism in soybean plants 18 , 19 , 32 , 37 , 53 , 54 , 57 , as found in this study (Figs. 1 b,d, 3 and 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Compared with the seed and leaf application methods, studies on soil Ni fertilization are more advanced, with a range of growing environments, soil classes and soybean genotypes having been evaluated previously (Table 3 ). It has been reported in the literature that this method improves N metabolism in soybean plants 18 , 19 , 32 , 37 , 53 , 54 , 57 , as found in this study (Figs. 1 b,d, 3 and 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…These results align with the findings of Zhou et al , where NiO and NiSO 4 at 50 mg kg −1 had no impact on soybean root and shoot biomass and length but significantly increased the grain yield (39 and 19%) and grain weight (26 and 12%); however, NiSO 4 at 200 mg kg −1 significantly decreased the root length (∼25 and 33%), shoot length (∼19 and 25%), root biomass (∼17 and 28%), shoot biomass (∼17 and 34%), grain yield (∼25 and 23%) and grain weight (∼9 and 29%) of soybean. 17 Conversely, NiCl 2 at 50 mg L −1 decreased the seed yield, pods per plant, and grain weight of Cicer arietinum L. in soil by 13, 24, and 9%, respectively and by 21, 34, and 13% at 100 mg L −1 . 20 The increased toxicity of NiCl 2 may be associated with its rapid dissolution.…”
Section: Resultsmentioning
confidence: 92%
“…43 Zhou et al reported that the application of NiSO 4 increased soybean protein content at 50 mg kg −1 by 12%, while 200 mg kg −1 decreased the value by 20%. 17 Chen et al revealed that polystyrene microplastics (2 mg kg −1 ) enhanced the protein content in Vigna radiata L. by 3%, while levels were reduced by 3% at 4 mg kg −1 . Similarly, Pb (20–40 μM) decreased the protein content by 9% and 18%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations